Homelander and The Ambiguity of Morality in the Television Series the Boys - Lingga Agung; Fahrezi Kalif Syahdanendra (Rekam, 2025)
Morality, as a dynamic component of culture, constantly shifts in response to social and ideological transformations. In the landscape of popular culture, the superhero figure has long served as a manifestation of moral values and an ethical compass for society. However, the series The Boys (2019) presents a deconstruction of this traditional representation through the character of Homelander, who symbolises moral ambiguity and corruption resulting from absolute power—standing in stark contrast to the idealised image of Superman. This study employed a qualitative method grounded in critical theory and Jacques Derrida’s deconstruction framework to examine how morality is represented and destabilised within the narrative of the series. Primary data were collected from selected episodes across three seasons of The Boys, focusing on three key scenes: the airplane incident in Season 1, Episode 4; the confrontation with Blindspot; and Homelander’s public speech in Season 3. Analysis was conducted on dialogue, character interactions, and visual aesthetic elements such as costume symbolism, lighting, and camera composition. Secondary data consisted of scholarly articles, books, and theoretical texts discussing superhero morality, Derrida’s deconstruction, and media representation politics. The analytical process involved three interrelated approaches: (1) narrative analysis to explore story structure and character development; (2) visual analysis to interpret symbolic and aesthetic elements that construct Homelander’s moral image; and (3) deconstructive analysis to apply the concepts of différance, trace, and critique of grand narratives and binary oppositions within discourses of heroism. The findings indicate that Homelander is not merely a symbol of moral decadence, but also a critique of capitalist institutions that exploit the superhero image for power and economic gain. From a deconstructive perspective, Homelander is not a fixed signifier, but a trace whose meaning is continually deferred and shaped by the forces of capitalism, media, and corporate spectacle. Thus, The Boys functions not only as entertainment but also as a reflective space for reexamining discourses on morality, heroism, and power in contemporary popular culture.